دراسة أثر طريقة التغذية بمركب عضوي في نمو وانتاجية محصول البطاطا Solanum tuberosum.L ونوعية الدرنات - عثمان, جنان (Latakia University Journal -Biological Sciences Series, 2014)
هدف البحث إلى دراسة تأثير طريقة التغذية بالمركب العضوي"Plant energy1000" في نمو وإنتاجية محصول البطاطا ونوعية الدرنات (الصنف رومانو)، وتضمن أربع معاملات: شاهد وثلاث طرق للتغذية بالمركب العضوي، تغذية جذرية، تغذية ورقية، تغذية جذرية وورقية معاً. نفذ البحث في مشتل جامعة تشرين في عروة ربيعية للموسم الزراعي 2012، واعتمد تصميم العشوائية الكاملة في تنفيذ البحث. أظهرت النتائج أن تغذية النباتات بالمركب العضوي أدى - بصورة عامة- إلى زيادة نمو النباتات، الأمر الذي تجلى في زيادة الوزن الرطب، ومساحة المسطح الورقي ودليله، وكذلك في زيادة عدد الدرنات والإنتاجية الإجمالية والتسويقية، فضلاً عن تحسين نوعية الدرنات، وكان هذا بمجمله أكثر وضوحاً عندما اتبعت طريقة التغذية الجذرية والورقية معاً بالمركب العضوي والتي أظهرت تفوقاً معنوياً في زيادة الإنتاج وتحسين نوعيته. This research aims to study the effect of different treatments of potato plants with a feeding organ on the growth and yield of potato crop and on the quality of tubers. The Romano variety of potato was used, and the commercial organic feeder "plant energy 1000" was applied in four treatments. The treatments were: a control and three ways for treating the plants with the organic feeder: by roots, foliage spray, and by both in one treatment. The completely randomized design was adopted in this experiment. The experiment was implemented in the nursery farm of Tishreen University in the spring planting season of 2012. The results showed that treating potato plants with the organic feeder led in general to an increase in the growth, which was reflected in the increase in the fresh weight, total leaf area and its indication, as well as in the quality and number of tubers, total production and marketing quality. These results were clearer in the case of the joint treatment: root feeding and foliage spray together. This treatment showed significant superiority in increasing production and improving its quality.